Designing, Implementing and Analyzing a Responsive Teaching Professional Development for Biology Graduate Student Teaching Assistants - Simon, Matthew. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Education.; Advisor: Julia Gouvea.; Committee: David Hammer, Mitch McVey, and Rachel Scherr.; Keywords: Science education, and Education.